Radość w Psalmach - WITCZYK, Henryk (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Joy and agony constitute two leitmotifs of the Book of Psalms, the former being expressed predominantly in the hymns, which comprise songs of adoration and worship. It is God, through his various doings, that provides the essential source of joy in the Psalms. The fundamental doing of God is the work of creation, which inspires delight in its magnitude and stimulates exultant praise of the Creator. «Rejoicing in the creation» is closely intertwined with «rejoicing in the gift.» This basic form of joy is inspired by the earthly gifts with which God showered the humankind and which he incessantly offers to human beings. These earthly goods are perceived as direct and personal gifts from God to the human being, who trusts him and obeys the Law of the Covenant. An equally great joy is experienced by Israel in the face of the acts of the Divine power which determines the course of history. Divine justice also restores the joy lost due to sin. The greatest of all joy, true happiness indeed, is provided by God’s love, as well as by the hope for a life in communion with God in eternity: this hope indeed transforms into certainty. Joy, which is experienced in the Psalms in all these various ways and which has multifarious causes, finds its external expression in the exultant liturgy, in− formed with happiness, which is celebrated by Israel on the main festivals. Joy becomes then prayer. Translated by Dorota Chabrajska